2010
DOI: 10.1186/1471-2458-10-343
|View full text |Cite
|
Sign up to set email alerts
|

Change in depressive symptoms over higher education and professional establishment - a longitudinal investigation in a national cohort of Swedish nursing students

Abstract: BackgroundThere are indications of a high prevalence of psychological distress among students in higher education and also that distress increases over the course of study. However, not all studies on student distress controlled for sociodemographic differences and few followed development of distress over an extended period through professional establishment. We investigated if there is an independent effect of time in education and the first two years in the profession on depressive symptoms and mapped chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
2
13
1
6
Order By: Relevance
“…Longitudinal studies have confirmed that nursing students' psychological distress increases significantly during their education (Christensson, Runeson, Dickman, & Vaez, 2010;Deary, Watson, & Hogston, 2003;Lo, 2002;Nerdrum, Rustoen, & Ronnestad, 2009;Watson et al, 2009). …”
Section: Psychological Distress Among Nurses and Nursing Studentsmentioning
confidence: 94%
“…Longitudinal studies have confirmed that nursing students' psychological distress increases significantly during their education (Christensson, Runeson, Dickman, & Vaez, 2010;Deary, Watson, & Hogston, 2003;Lo, 2002;Nerdrum, Rustoen, & Ronnestad, 2009;Watson et al, 2009). …”
Section: Psychological Distress Among Nurses and Nursing Studentsmentioning
confidence: 94%
“…Porém, um estudo sobre qualidade de vida relacionada à saúde e sintomas depressivos de estudantes de graduação em enfermagem indicou prejuízo multidimensional na qualidade de vida e observou-se que o impacto negativo na percepção de bem-estar é maior nos estudantes do último ano do curso (23) . Destacam-se como estressores pouca/nenhuma oportunidade para o lazer, agenda lotada, experiência clínica/estágios, currículo da instituição, sobrecarga de atividades, distância diária percorrida entre a residência e a universidade, período integral do curso, falta de tempo para atividades extracurriculares, desorganização das disciplinas, relacionamento conflituoso com os docentes, alto grau de exigência durante o período dos estágios curriculares, curtos prazos para entrega de trabalhos, falta de ética profissional, competitividade entre os alunos, gastos financeiros, atraso no tempo de formação, superlotação das classes e situações que requerem relação interpessoal (13,17,21,22,(24)(25)(26)(28)(29)(30)32,33) . Estes fatores estressores podem ocasionar desordens psicológicas e físicas (fadiga, ansiedade e cansaço), afetando a vida acadêmica e em consequência o futuro profissional, pois há comprometimento do cotidiano do aluno.…”
Section: Resultsunclassified
“…Estes fatores estressores podem ocasionar desordens psicológicas e físicas (fadiga, ansiedade e cansaço), afetando a vida acadêmica e em consequência o futuro profissional, pois há comprometimento do cotidiano do aluno. Sendo as alterações de saúde: depressão, ansiedade, estresse, aumento do sentimento raiva, angústia, desespero, mau humor, má qualidade do sono, uso de álcool, cansaço e fadiga (11)(12)(13)(14)16,(18)(19)(20)26,28,(29)(30)(31)(32)(33) , descritas como transitórias e de fácil superação pelos estudantes investigados.…”
Section: Resultsunclassified
“…Longitudinal studies have confirmed that nursing students' psychological distress increases significantly during their education (Christensson, Runeson, Dickman, & Vaez, 2010; www.professionsandprofessionalism.com Page 3 Watson, & Hogston, 2003;Lo, 2002;Nerdrum, Rustoen, & Ronnestad, 2009;Watson et al, 2009). …”
Section: Psychological Distress Among Nurses and Nursing Studentsmentioning
confidence: 98%